2007
DOI: 10.1144/jm.26.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Latest Permian deep-water ostracods from southwestern Guangxi, South China

Abstract: A very diverse ostracod fauna was discovered in the latest Permian strata of the Dongpan section, southwestern Guangxi, South China. Fifty-one species belonging to twenty-eight genera were identified and described, including two new species (Bairdia dongpanensis n. sp. and Spinomicrocheilinella anterocompressa n. sp). This type of assemblage, with nineteen palaeopsychrospheric species and four pelagic species, is the first world-wide deep-water ostracod fauna reported from the latest Permian strata and the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…This is typical of radiolarian survival stage across the PTB in other parts of the world. It is notable that the thin shell psychrophilic ostracods experienced similar stages at the Dongpan Section (Yuan et al, 2006).…”
Section: The Extinction Episodes Of Late Changhsingian Organisms At Dmentioning
confidence: 92%
See 1 more Smart Citation
“…This is typical of radiolarian survival stage across the PTB in other parts of the world. It is notable that the thin shell psychrophilic ostracods experienced similar stages at the Dongpan Section (Yuan et al, 2006).…”
Section: The Extinction Episodes Of Late Changhsingian Organisms At Dmentioning
confidence: 92%
“…3) This section has been extensively investigated for its lithology (Meng et al, 2005), sedimentology (Meng et al, 2004), clayrocks (Zhang et al, 2006a), carbon isotope , radiolarians (Feng et al, 2006a, b, c), foraminifers , brachiopods (He et al, 2005a), ostracods (Yuan et al, 2006), bivalves (He et al, 2007a) and ammonoids (Bu et al, 2006). The PTB was delineated between beds 13 and 12 by typical Permian and Triassic ammonoids .…”
Section: Advances On Other Signatures Of Eventsmentioning
confidence: 99%
“…Triassic of the Alps (Kozur 1972) and Romania (Crasquin‐Soleau and Gradinaru 1996). A Late Permian fauna from South China has also been discovered recently (Yuan et al. 2007).…”
Section: Systematic Palaeontology
(S Crasquin)mentioning
confidence: 99%
“…It is a continuous section from the latest Permian to the Early Triassic, and provides unique materials for study of biotic and environmental changes in deep-water facies during the Permian-Triassic transition. The end-Permian fossils at this section are abundant, including radiolarians [16][17][18][19][20] , brachiopods [21,22] , bivalves [23] , cephalopods [24] , foraminiferas [25] and ostracods [26] . Meng et al [27] reported the Upper Permian Changhsingian bivalves including Claraia liuqiaoensis, Euchondria jingxianensis, Posidonia sp., Nuculopsis sp.…”
mentioning
confidence: 99%